Impacts characterisation in Rugby Union - Lokteff, F.; Canet, R.; Drissi, S.; Moretto, P. (Computer Methods in Biomechanics and Biomedical Engineering, 2020)
Rugby Union is a collective sport where athletes endure contacts during different phases of the play (tackles, rucks, mauls and scrums). These events have to be characterised in term of intensity, number and dangerousness while they also influence the physical fitness of the players (Johnston et al. 2014) and are sometimes linked to direct or delayed injuries (Brooks et al. 2005). Brooks and some authors have concluded that rugby union games cause serious damage to the musculoskeletal system. More recently, the risks of damage to the spinal and cerebral nervous structures are also described following the increasing number of concussions recorded (Gabbett et al. 2010). Given the importance of the task which involves the safety of the players, the staff devote considerable time to analyse contacts in an attempt to guarantee effective monitoring and to plan training and recovery adapted to the workload and the contacts experienced during training and during matches. Today, GPS (Global Positioning System) including inertial unit (accelerometer, magnetometer and gyroscope) are worn by the players during the match and training. The one developed by Catapult Innovations has been validated by Gabbett et al. (2010) to detect an impact when the body changes orientation (> 60° forward,> 45° left or right,> 30° rear) and that the acceleration varies significantly. Our work is the first attempt at using it to characterise the impacts endured by the players during the 2018 and 2019 seasons of an elite team of the French rugby championship. The purpose of this study is to describe the significant differences in intensity and number of impacts for each position in rugby union in order to determine a risk profile.